Coplanar Waveguide Microwave Sensor for Label-Free Real-Time Glucose Detection - M. Sameer; P. Agarwal (Radioengineering, 2019)
In this work, a~real-time label-free microwave diagnostic approach using Co-Planar Waveguide (CPW) design has been demonstrated for glucose detection. This mechanism has tremendous potential for the biomedical applications. Here, glucose biosensor is implemented with 50 Ω CPW transmission line, where the centre localized 3 mm diameter of CPW transmission line has been used for the sensing. Glucose sensor is implemented utilizing low cost multilayer PCB and polymer Poly-Di-Methyl-Siloxane(PDMS) fabrication technology. CPW transmission line is fabricated on FR4 microwave laminate board. To confine the Analyte Under Test (AUT) on the sensing area, PDMS polymer cavity is configured in the centre of CPW transmission line. The electromagnetic interaction with the varying dielectric constant of Glucose:DI water solution results shift in S11 parameter, which is closely observed to use as the source of sensing. CPW based glucose sensor is experimentally measured for S11 parameter using VNA, with varying glucose concentration range from 0 mg/ml (only DI water) to 4 mg/ml with the interval of 1 mg/ml. The measured results showed good sensitivity of 108.4 MHz/mg/ml and high accuracy with good linear regression coefficient of 0.9979.